The Role of Virtual Communities in Encouraging Social Interaction in the Digital Era - Aulia Iswaratama (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Virtual communities have become a significant platform in facilitating social interaction in the digital era. With the development of information and communication technology, individuals can connect with each other without being limited by geographic boundaries. This article discusses the role of virtual communities in providing diverse social interactions, allowing individuals to share knowledge, interests, and experiences with fellow community members. Apart from that, this article will also discuss how virtual communities are able to facilitate the formation of strong social relationships, support the exchange of useful information, and expand individual social networks. Thus, virtual communities are not only spaces for social interaction, but also places where individuals can develop their social identities in a positive way.